California Bearing Ratio (CBR) of Engineered Sand Backfill Admixed with Recycled Tyre Wastes - Ahmad Shahrul Ahmad Azam,; Salina Sani,; Chan Chee Ming, (Progress in Engineering Application and Technology, 2024)
This study investigates the California Bearing Ratio (CBR) of engineered sand backfill admixed with recycled tire wastes, to determine whether using sustainable materials in geotechnical applications is feasible. In this study, CBR tests are systematically evaluated for three different mix ratios: 100% sand, 80% sand and 20% rubber granule, and 60% sand and 40% rubber granule, both with and without stabilizer. Further research shows the effect of stabilizers and recycled tire wastes on the mechanical properties of the engineered backfill, whereas initial CBR testing on the 100% sand samples set a standard strength performance. The results show that adding rubber granules significantly reduced the CBR values, highlighting the need to take additional measures to improve strength. A major approach to mitigate the reduction is to add a stabilizer, which is shown by the significant increases in CBR values observed, especially with longer curing times. After 7 days of curing, an 80S20R mixture with a stabilizer is the optimal mix ratio for improved strength. This mixture showed promising performance. This study provides a viable backfill material substitute and important new insights into potential applications of recycled tire wastes in geotechnical engineering. The results not only address the engineering aspects of the mixture but also provide opportunities for additional research, such as a thorough evaluation of the long-term mechanical behavior and the optimization of stabilizer content.